The influence of personality traits on leadership styles among student leaders in Malaysian public universities - Mohd Nasir, Muhammad Az Zuhri; Ma’rof, Aini Azeqa; Rosnon, Mohd Roslan (Human Resource Management Academic Research Society, 2024)
This study investigates the influence of personality traits on leadership styles among student leaders in Malaysian public universities. Using the Big Five Personality Traits framework, the research examines how traits like extraversion, agreeableness, conscientiousness, neuroticism, and openness shape people-oriented and task-oriented leadership. A diverse sample of 400 student leaders was analyzed through quantitative methods, including correlation and regression analyses. The results indicate that extraversion and agreeableness are strongly associated with people-oriented leadership, while conscientiousness is a significant predictor of task-oriented leadership. Neuroticism was found to negatively impact both leadership styles, suggesting emotional instability may hinder leadership effectiveness. These findings highlight the critical role of personality traits in shaping leadership behaviors and underscore the need for leadership development programs that align with individual personality profiles. This study provides valuable insights into leadership development in the multicultural context of Malaysian public universities. It also contributes to a broader understanding of how personality influences leadership, offering practical implications for designing tailored leadership programs that enhance both relational and goal-oriented leadership skills.